Medication Therapy Management Services Provided by Student Pharmacists - Hata, Micah (American Journal of Pharmaceutical Education, 2012)
Objectives. To evaluate the impact of student pharmacists delivering medication therapy management (MTM) services during an elective advanced pharmacy practice experience (APPE). Methods. Student pharmacists provided MTM services at community pharmacy APPE sites, documented their recommendations, and then made follow-up telephone calls to patients to determine the impact of the MTM provided. Students were surveyed about the MTM experience. Results. Forty-seven students provided MTM services to 509 patients over 2 years and identified 704 drug-related problems (average of 1.4 problems per patient). About 53% of patients relayed the recommendations to their physician and 205 (75%) physicians accepted the recommendations. Eighty-eight percent of patients reported feeling better about their medications after receiving MTM services. A majority of the students perceived their provision of MTM services as valuable to their patients. Conclusions. Providing MTM services to patients in a pharmacy practice setting allowed student pharmacists to apply skills learned in the doctor of pharmacy (PharmD) curriculum.